2016
DOI: 10.1007/s13412-016-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in the nexus

Abstract: Synthetic nitrogen (N) fertilizer has enabled modern agriculture to greatly improve human nutrition during the twentieth century, but it has also created unintended human health and environmental pollution challenges for the twentyfirst century. Averaged globally, about half of the fertilizer-N applied to farms is removed with the crops, while the other half remains in the soil or is lost from farmers' fields, resulting in water and air pollution. As human population continues to grow and food security improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 62 publications
2
18
0
4
Order By: Relevance
“…Soil N mining could be overestimated if N inputs from irrigation water, rainfall, crop residue, biological N fixation, and atmospheric deposition are ignored, but could be underestimated if losses through leaching, erosion, runoff, volatilisation, and denitrification are ignored (Majumdar et al 2016). The N footprint tool is useful for identifying hotspots of N losses to the environment, simulating mitigation options, and informing policy decisions for good N management through raising awareness of social responsibilities Davidson et al 2016). The application of the tool showed that in many countries the largest portion of the N footprint was associated with food production, with N accumulation in selected countries like the United States of America, whereas N mining occurred in countries like Tanzania in SSA (Hutton et al 2017).…”
Section: Table 3 Effect Of Adding Phosphorus (P) and Potassium (K) Tmentioning
confidence: 99%
“…Soil N mining could be overestimated if N inputs from irrigation water, rainfall, crop residue, biological N fixation, and atmospheric deposition are ignored, but could be underestimated if losses through leaching, erosion, runoff, volatilisation, and denitrification are ignored (Majumdar et al 2016). The N footprint tool is useful for identifying hotspots of N losses to the environment, simulating mitigation options, and informing policy decisions for good N management through raising awareness of social responsibilities Davidson et al 2016). The application of the tool showed that in many countries the largest portion of the N footprint was associated with food production, with N accumulation in selected countries like the United States of America, whereas N mining occurred in countries like Tanzania in SSA (Hutton et al 2017).…”
Section: Table 3 Effect Of Adding Phosphorus (P) and Potassium (K) Tmentioning
confidence: 99%
“…In fact, considering the relationship between N Input -N Output and Output N proposed by Norton et al (2015), EI is in a situation of "Farmer wins, Environment wins" and our FP treatments are in the situation of "Farmer loses, Environment loses", which is coincident with the average estimation for Argentina. Similarly, following Davidson et al (2016), EI is close to the situation of "Food security wins, Environment wins", but FP aligns with "Food security wins, Environment loses -soil degradation".…”
Section: Nitrogen Productivitymentioning
confidence: 91%
“…Currently, this process involves engaging scientists from member universities, NGOs, and the USDA and in some instances can involve broader engagement of the scientific community (Snyder, 2015) and specific contracts for meta‐analyses or model applications. Beyond engaging scientists in direct evaluation of metrics, such metric improvements over the long term may increasingly depend on the development and availability of models capable of accurately simulating both complex biophysical and biogeochemical processes, including fate of applied nutrients (Davidson et al, 2016) and the dynamics of soil carbon (Paustian et al, 2016), and management practices that influence these processes.…”
Section: Measurement Of Field‐scale Environmental Outcomesmentioning
confidence: 99%